Inhibitory Effect of Ethanolic Extract Isolated from Radix Pulasatillae Seeds against Proliferation of A549 Human Lung Cancer Cells - Ali Al-Shawi (University of Thi-Qar Journal of Science, 2019)
The present study was evaluated the anticancer activity of Radix Pulsatillae ethanol extract at first by using high throughput screening HTS for herb fractions screening in concentration of 100μM to identify the active fraction andthen we measured the cytotoxic effects by using morphology changes, and detected apoptosis by Hoechst 33258staining. Our results showed that Radix Pulsatillae ethanol extract has a strong toxicity against A549 lung cancer cellsand low toxicity with mice normal splenocytes and requires more investigation to identify the small natural moleculewith new anticancer activity and further mechanistic for cancer pathways